The Effect Of Watching Intensity On Purchase Intention Through Parasocial Relationship And Perceived Source Credibility In Edtech Program - Nur Asy Syifa Priatna; Siti Aisyah; Aqwa Naser Daulay (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2026)
The rapid growth of digital education has transformed the learning process into a competitive, content-driven platform ecosystem. This study examines the effect of watching intensity on purchase intention in the Clash of Champions program produced by Ruangguru. Grounded in Media Psychology Theory, Parasocial Relationship Theory, Source Credibility Theory, and the Elaboration Likelihood Model, this research tests a parallel mediation model involving parasocial relationships and perceived source credibility. A quantitative survey of 406 Indonesian high school and university students was conducted and analyzed using PLS-SEM with SmartPLS 4. The results show that watching intensity significantly affects purchase intention, parasocial relationships, and perceived source credibility. Parasocial relationships and perceived source credibility also significantly influence purchase intention. Furthermore, parasocial relationships significantly mediate the relationship between watching intensity and purchase intention, whereas perceived source credibility does not mediate this relationship. These findings suggest that emotional-relational mechanisms play a more decisive role than credibility evaluations in driving subscription intentions within competition-based EdTech platforms.